Text Messaging Real-Time COVID-19 Clinical Guidance to Hospital Employees - Williams, Cheyenne; Rao, Aditi; Ziemba, Justin B.; Myers, Jennifer S.; Patel, Neha (Applied Clinical Informatics, 2021)
Background During the initial days of the coronavirus disease 2019 (COVID-19) pandemic, hospital-wide practices rapidly evolved, and hospital employees became a critical population for receiving consistent and timely communication about these changes.Objectives We aimed to rapidly implement enterprise text messaging as a crisis communication intervention to deliver key COVID-related safety and practice information directly to hospital employees.Methods Utilizing a secure text-messaging platform already routinely used in direct patient care, we sent 140-character messages containing targeted pandemic-related updates to on-duty hospital employees three times per week for 13 weeks. This innovation was evaluated through the analysis of aggregate “read” receipts from each message. Effectiveness was assessed by rates of occupational exposures to COVID-19 and by two cross-sectional attitudinal surveys administered to all text-message recipients.Results On average, each enterprise text message was sent to 1,997 on-duty employees. Analysis of “read” receipts revealed that on average, 60% of messages were consistently read within 24 hours of delivery, 34% were read in 2 hours, and 16% were read in 10 minutes. Readership peaked and fell in the first week of messaging but remained consistent throughout the remainder of the intervention. A survey administered after 2 weeks revealed that 163 (79%) users found enterprise texts “valuable,” 152 (73%) users would recommend these texts to their colleagues, and 114 (55%) users preferred texts to email. A second survey at 9 weeks revealed that 109 (80%) users continued to find texts “valuable.” Enterprise messaging, in conjunction with the system's larger communication strategy, was associated with a decrease in median daily occupational exposure events (nine events per day premessaging versus one event per day during messaging).Conclusion Enterprise text messages sent to hospital-employee smartphones are an efficient and effective strategy for urgent communications. Hospitals may wish to leverage this technology during times of routine operations and crisis management.
Keywords: COVID-19; smartphones; in-hospital communication; secure messaging